Ilm al-Maʿājim wa al-Muʿjam al-ʿArabī - Saiful Anwar (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2015)
A dictionary is a reference work that contains the vocabulary of a language, usually arranged alphabetically, with definitions of each entry and information concerning its forms, pronunciation, etymology, meanings, and various usages. It is a systematically organized list of words from a language compiled according to a particular methodology. A dictionary may also serve as a tool for clarifying the meanings of foreign words. The study of dictionaries encompasses both lexicology and lexicography. Lexicology focuses on the scientific study of words, including their structure, formation, meanings, and linguistic characteristics. Lexicography, on the other hand, is concerned with the compilation and classification of dictionaries, the selection of lexical entries, the methodology of dictionary compilation, the objectives of dictionary making, and the meanings of the words included. This article discusses these two major fields—lexicology and lexicography—in the context of the Arabic language, which is recognized as one of the richest languages in the world because of its vast vocabulary and diverse semantic expressions. Lexicographical studies in Arabic differ in several respects from those conducted in other living languages around the world.